Global finance in crisis - Konings, Martijn; Panitch, Leo (Papeles de Europa, 2009)
This essay examines the questions raised by the present financial crisis through an enquiry into the institutional foundations of American finance. We view with some skepticism strong claims concerning the disastrous outcome for the structural dynamism of the global financial system and America's position in it. Many critical political economists tend to take the system of global financial markets as their point of departure and then locate the US in this system. Such approaches, however, generally fail to do justice to the decades-long build up of US financial power and do not capture many of the organic institutional linkages through which the American state is connected to the world of global finance and which are responsible for its imperial sprawl. In many ways, financial globalization is not best understood as the re-emergence of international finance but rather as a process through which the expansionary dynamics of American finance took on global dimensions. Because the present system of global finance has been shaped so profoundly by specifically American institutions and practices, it will not do to evaluate the changes and transformations of this system on the basis of either an abstract, generic model of capitalism or mere extrapolations from conjunctural crises. Crisis and instability are part and parcel of the dynamics of imperial finance and so are the managerial capacities developed by the US state. The most important questions that should occupy critical political economists therefore have to do not with what appear to be external challenges to US financial power (or the putative opportunities for progressive change opened up by them), but rather relate to the ways in which the imperial network of intricate, complex and often opaque institutional linkages between the US state and global finance is managed and reproduced.
Keywords: United States; Imperialism; Finance; Globalization; Subprime crisis